Musings on methodology - Hertog, Erik; Van Gucht, Jan; de Bontridder, Leen (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
As an applied science, community interpreting research is often tributary to the social sciences for its methods. Indeed, focus groups, interviews, questionnaires and case studies, in other words both quantitative and qualitative surveys and analyses are part and parcel of the social sciences methodology and are becoming increasingly common in CI research as well.But, as is often the case with applied scientific research, when it comes to adopting the methodological orthodoxy of the parent science, it is sometimes found lacking in methodological coherence and rigour. In our view, the most commonly found methodological hiatus in the current empirical CI research literature is the (mis)use of research designs of an essentially exploratory nature to generate broad sweeping conclusions at medium or even grand theory level, typically resulting in a total lack of falsifiability.A second point of concern is a rather generalised lack of validation of the outcomes of field research. That is why this article proposes a critical reflection on empirical research methodology in the field of community based interpreting in the form of a tentative typology of research methodologies, illustrated with an example taken from the authors’ own research.